Partial portal vein arterialization during living-donor liver transplantation: a case report - Yasuhiro Maruya; Masaaki Hidaka; Florian Pecquenard; Alzhan Baubekov; Yuki Nunoshita; Shinichiro Ono; Tomohiko Adachi; Mitsuhisa Takatsuki; Katsumi Tanaka; Shinichiro Ito; Kengo Kanetaka; Susumu Eguchi (Surgical Case Reports, 2020)
Abstract Background Hepatic artery thrombosis can lead to graft loss associated with severe hepatic infarction or bile duct ischemia. When anatomical hepatic artery reconstruction is impossible in liver transplantation or hepato-pancreatic biliary surgery, portal vein arterialization (PVA) is proposed as a salvage technique. Herein, we report our experience with a case that showed favorable clinical outcomes after partial PVA during living-donor liver transplantation (LDLT) because of difficulties in arterial reconstruction. Case presentation A 62-year-old woman with non-B, non-C liver cirrhosis complicated with hepatocellular carcinoma was being prepared for LDLT using an extended left lobe graft. The graft presented with two arteries (left hepatic artery, 2 mm; middle hepatic artery, 2 mm). The first anastomosis was performed using the recipient hepatic artery stumps, but no flow was detected on Doppler control because of thrombus formation. The next attempt was executed using the middle colic artery with a radial artery jump graft and the right gastroepiploic artery, but it led to the same result. Thus, the graft oxygen support by the standard arterial procurement was abandoned, and a shunt was created between the ileocecal artery and the vein to obtain PVA. Arteriography of the superior mesenteric artery showed that the shunt was relatively patent, and the portal vein was apparent. No biliary complication or liver abscess occurred postoperatively, and the patient presented with good liver function and no complications related to portal vein hypertension, nor liver fibrosis 18 months after the LDLT. Conclusion Partial PVA with a shunt created between the ileocecal artery and the vein is useful when arterial reconstruction is difficult during LDLT for preventing graft loss caused by severe hepatic infarction or bile duct ischemia.